Legal Analysis of Inconsistencies in Child Marriage Regulations - Eko Budianto Tomayouw; Suwarti Suwarti; Nam Rumkel (Jurnal Indonesia Sosial Sains, 2024)
This study analyzes the inconsistencies in child marriage regulations in Indonesia, which result in legal uncertainty in efforts to protect children through the marriage dispensation process. By employing both normative and sociological approaches, the study examines the legal implications of these regulatory disparities and assesses the marriage dispensation process from a benefit-based perspective. The findings reveal that the inconsistency in regulations leads to unequal legal protection for children involved in marriage, highlighting the urgent need for harmonizing laws and strengthening child protection mechanisms. Improvements are necessary not only in the Child Protection Law but also in the revision of the Marriage Law, taking into account the broader responsibility of the state in safeguarding children. Although the Marriage Law sets a minimum age for marriage, it still allows for loopholes through marriage dispensation, reflecting an inconsistency in legislative efforts to protect children. The overlap between different legal provisions creates uncertainty in the legality of child marriages, as different interpretations of the laws can lead to varying legal outcomes. This study identifies two key issues: the legal consequences of regulatory inconsistencies in child marriages and how marriage dispensation is viewed from a benefit perspective. Using a normative legal research method, the study draws on primary, secondary, and tertiary legal sources, including legislation and court decisions, and analyzes the data qualitatively. The results indicate that the regulatory inconsistencies create legal uncertainty in the protection of children in marriages approved through dispensation. Therefore, protecting these marriages from a benefit perspective is essential, as the dispensation process serves as a form of legal protection for children, rather than defying the rule of law.